Educational Chain Whisper Game for Improving Listening and Memory Based on Local Wisdom - Ahsanurrijal; Akbar, Fadly; Ahmad, Ahmad; Abdullah, Ahmad Rizal; Ramli, Aswadi (PT. Lontara Digitech Indonesia, 2025)
This community service is focused on improving students' listening and memory skills through the implementation of an educational